Comparative Study on Deposit Mobilization of Nepal Bank Limited and Sanima Bank Limited - Shrestha, Manisha; Aryal, Rameshower (Journal of Kathmandu BernHardt College, 2022)
This study focuses on and compared the deposit mobilization condition of Nepal Bank Limited (NBL) and Sanima Bank Limited (SBL). Taking sample the two banks as a sample, this study tries to find the effects of profitability and loan and advance on deposit mobilization from the secondary data 2011 to 2020. The study's findings indicate that the return on assets and earnings per share have a significant and positive impact on the profitability performance of sample banks.